Quantitative MRI comparison of early and late parenchymal injury after transcallosal vs. endoscopic approaches for third ventricle colloid cysts - Erginoglu, Ufuk; Eisenmenger, Laura; Elshamy, Walid; Ataoglu, Cagdas; Armstrong, Stephanie A.; Olsen, Halli T.; Sulaimanov, Umid; Ross, Jordan; Samsonov, Alexey; Ak, Huseyin Erdem; Aycan, Abdurrahman; Keles, Abdullah; et al. (Frontiers in Surgery, 2025)
BackgroundThe interhemispheric transcallosal (ITA) and endoscopic approaches (EA) are established treatments for third ventricle colloid cysts (TVCCs); however, their relative parenchymal impact and the progression of associated MRI changes from early to late postoperative stages remain undefined.ObjectiveTo compare early volumetric MRI findings after ITA and EA for TVCC resection and determine whether early parenchymal injury persisted on late imaging.MethodsTwenty-three patients (ITA, 13; EA, 10) with early and late postoperative MRI were retrospectively reviewed. Early T2/FLAIR hyperintensity volumes were segmented along the surgical tract (burr-hole tract subtracted in EA). DWI/ADC imaging assessed diffusion restriction. Late MRI evaluated gliosis, encephalomalacia, and parenchymal loss. Statistical, correlation, and sensitivity analyses assessed associations while adjusting for cyst size and hydrocephalus.ResultsEarly MRI hyperintensity volume was smaller after ITA than EA (349 ± 218 mm3 vs. 2,952 ± 2,084 mm3; p < 0.001). Diffusion restriction occurred in 7.7% of ITA and 50% of EA (p = 0.052). Gliosis, encephalomalacia, and parenchymal loss on late MRI were absent after ITA but present in 50% of EA cases (p = 0.007 each), with larger early volumes in EA associated with gliosis (p = 0.032), encephalomalacia, and parenchymal loss (p = 0.016 each). These associations persisted after adjusting for cyst size and hydrocephalus. Gross total resection occurred in 92% of ITA and 50% of EA cases (p = 0.039).ConclusionsCompared with ITA, EA produced larger early parenchymal injury, half of which persisted as structural abnormalities on late imaging, indicating more persistent radiologic change.